Nexus between economic sanctions and inflation: a case study in Iran - Ghorbani Dastgerdi, Hamidreza; Yusof, Zarinah; Shahbaz, Muhammad (Taylor & Francis, 2018)
Conventional studies have applied dummy variables to analyse the relationship between economic sanctions and inflation while we construct an index which is called Trade-Financial Sanctions (TF index). TF Index is a liner combination of indices which includes trade openness and foreign investment by applying the principal component model. Through the TF index and market exchange rate the impact of economic sanctions on inflation is analysed in the three phases of sanctions; free sanctions, heavy sanctions, and light sanctions. The results illustrate that the TF index decreases inflation when the Iran’s economy experiences free sanctions or light sanctions relative to when the economy is in heavy sanctions. Heavy sanctions create instability in the market exchange rates and widening the gap between the market and the official exchange rates. Furthermore, economic sanctions increase expected inflation among the people and drive higher inflation. Therefore, these results suggest that the government should work more seriously to solve the main obstacles of trade and investment inflows imposed by the economic sanctions.